Complementary metal-oxide-semiconductor (CMOS) charge pump with temperature variation for self-powered applications - Nurul Adlina, Johari (2023)

(untitled)
This research introduces an innovative CMOS charge pump topology that addresses the challenge of maintaining a steady 1V output voltage across a wide temperature range. Through the integration of a closed-loop regulation circuit, the charge pump demonstrates remarkable stability and tolerance to temperature changes, ensuring consistent performance in self-powered devices. Furthermore, the successful integration of a MOSFET-based DC-to-DC converter within the charge pump mechanism achieves efficient voltage boosting, enhancing output stability. Rigorous simulations validate the design's feasibility and suitability for real-world self-powered applications. This study contributes to the advancement of self-powered devices by offering a reliable solution for voltage regulation under varying temperature conditions.